Expanding the Substrate Specificity of Thermoanaerobacter pseudoethanolicus Secondary Alcohol Dehydrogenase by a Dual Site Mutation. Issue 6 (13th February 2018) - Musa, Musa M.; Bsharat, Odey; Karume, Ibrahim; Vieille, Claire; Takahashi, Masateru; Hamdan, Samir M.
Abstract : Here, we report the asymmetric reduction of selected phenyl‐ring‐containing ketones by various single‐ and dual‐site mutants of Thermoanaerobacter pseudoethanolicus secondary alcohol dehydrogenase (TeSADH). The further expansion of the size of the substrate binding pocket in the mutant W110A/I86A not only allowed the accommodation of substrates of the single mutants W110A and I86A within the expanded active site but also expanded the substrate range of the enzyme to ketones bearing two sterically demanding groups (bulky–bulky ketones), which are not substrates for the TeSADH single mutants. We also report the regio‐ and enantioselective reduction of diketones with W110A/I86A TeSADH and single TeSADH mutants. The double mutant exhibited dual stereopreference to generate the Prelog products most of the time and the anti‐Prelog products in a few cases. Abstract : The enlarged substrate binding pocket of Thermoanaerobacter pseudoethanolicus secondary alcohol dehydrogenase W110A/I86A double mutant (W110A/I86A TeSADH) enables the asymmetric reduction of ketones bearing two sterically demanding groups. W110A/I86A TeSADH also reduced ketones that are substrates for W110A TeSADH single mutant with high enantioselectivity.